2010
DOI: 10.1111/j.1747-0285.2010.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel chalcones and 1,3,5‐triphenyl‐2‐pyrazoline derivatives as antibacterial agents

Abstract: The authors Ponnurengam Malliappan Sivakumar, Suresh Ganesan and Prabhawathi Veluchamy wishes to dedicate this work to their guide Prof MD on the occassion of his birthdayNovel sixteen chalcones and thirteen 1,3,5-triphenyl-2-pyrazolines were synthesized and characterized using FT-IR, HR-Mass, NMR ( C CoSY) and XRD. These compounds were evaluated for their antibacterial activity against six micro-organisms, namely Bacillus subtilis NCIM 2718, Staphylococcus aureus NCIM 5021, Salmonella typhi NCIM 2501, Enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 26 publications
(33 reference statements)
0
46
0
Order By: Relevance
“…It was observed that licochalcone A suppressed the growth of all the three tested bladder cancer cell lines in a dose-dependent manner (Figure 1). ERK 1/2 has been reported to be involved in drug resistance [11][12][13][14][15][16][17]. …”
Section: Effect Of Licochalcone a On Bladder Cancer Cell Growth And Ementioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that licochalcone A suppressed the growth of all the three tested bladder cancer cell lines in a dose-dependent manner (Figure 1). ERK 1/2 has been reported to be involved in drug resistance [11][12][13][14][15][16][17]. …”
Section: Effect Of Licochalcone a On Bladder Cancer Cell Growth And Ementioning
confidence: 99%
“…They exhibit anti-inflammatory [9], anti-invasive [10], anti-tumour [11] and antibacterial [12] properties. Chalcone treatment causes induction of apoptosis and alters mitochondrial membrane potential in various types of cancers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclization of chalcones, leading to pyridine, pyrimidine and pyrazoline derivatives, has been a developing field within the realm of heterocyclic chemistry for the past several years, because of their ready accessibility and the broad spectrum of biological activity of the products [38][39][40][41][42][43][44]. These observations led us to synthesize chalcones and its corresponding pyrazoline, exploring simple procedures.…”
Section: Open Accessmentioning
confidence: 99%
“…Many of these have been used as important intermediates in organic synthesis [1,2]. The compounds with the backbone of chalcones have been reported to possess various biological activities such as antimicrobial [3][4][5], antiinflammatory [6,7], antifungal [8,9], antioxidant [10,11], antileishmanial [12], antimalarial [13,14], antituberculosis [15,16], analgesic [17], anti HIV [18], antioxidant [19], antitumor [20,21] and neuro protective [22] activities.…”
Section: Introductionmentioning
confidence: 99%